2020
DOI: 10.1038/s41419-020-03021-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen glucose deprivation/re-oxygenation-induced neuronal cell death is associated with Lnc-D63785 m6A methylation and miR-422a accumulation

Abstract: Oxygen glucose deprivation/re-oxygenation (OGD/R) induces neuronal injury via mechanisms that are believed to mimic the pathways associated with brain ischemia. In SH-SY5Y cells and primary murine neurons, we report that OGD/R induces the accumulation of the microRNA miR-422a, leading to downregulation of miR-422a targets myocyte enhancer factor-2D (MEF2D) and mitogen-activated protein kinase kinase 6 (MAPKK6). Ectopic miR-422a inhibition attenuated OGD/R-induced cell death and apoptosis, whereas overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…By comprehensively considering the network-based predicted ranking, chemical structure, physicochemical properties, availability, and accessibility, these promising ingredients were selected for antistroke efficacy evaluation ( Figure 5 ). Subsequently, the OGD/R injury model, a recognized in vitro model in ischemic stroke research, was applied for pharmacological validation [ 46 , 47 ]. As shown in Figure 6 , the OGD/R insult group showed significantly lowered PC12 cell viability ( P < 0.01), while CA (6.25, 12.5, and 25 μ M), SCU (1, 2, and 4 μ M), chrisin (1, 2, and 4 μ M), fisetin (12 μ M), gallic acid (6.25 μ M), imperatorin (1, 2, and 4 μ M), and palmatine (3.125, 6.25, and 12.5 μ M) increased the viability of PC12 cells ( ∗ P < 0.05, ∗∗ P < 0.01, and ∗∗∗ P < 0.001, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…By comprehensively considering the network-based predicted ranking, chemical structure, physicochemical properties, availability, and accessibility, these promising ingredients were selected for antistroke efficacy evaluation ( Figure 5 ). Subsequently, the OGD/R injury model, a recognized in vitro model in ischemic stroke research, was applied for pharmacological validation [ 46 , 47 ]. As shown in Figure 6 , the OGD/R insult group showed significantly lowered PC12 cell viability ( P < 0.01), while CA (6.25, 12.5, and 25 μ M), SCU (1, 2, and 4 μ M), chrisin (1, 2, and 4 μ M), fisetin (12 μ M), gallic acid (6.25 μ M), imperatorin (1, 2, and 4 μ M), and palmatine (3.125, 6.25, and 12.5 μ M) increased the viability of PC12 cells ( ∗ P < 0.05, ∗∗ P < 0.01, and ∗∗∗ P < 0.001, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…5 , 7 Various m6A demethylases are called “erasers”, including fat mass and obesity-associated protein (FTO) and ALKB family member 5 (ALKBH5), which function is to reduce the modified RNA to the original RNA. 8 In addition, m6A binding protein acts as a “reader” and mainly includes the YT521-B homology (YTH) and heterogeneous nuclear ribonucleoprotein (HNRNP) families, such as HNRNPC, YTHDC1, YTHDC2, YTHDF1 and YTHDF2, which recognize m6A-modified RNA and thus regulate mRNA metabolism and function. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…The expression of m 6 A erasers, ALKBH5 and FTO, are decreased but not writers. Overexpression of m 6 A erasers can alleviate neuronal damage induced by I/R injury ( Xu S. et al, 2020 ). A third study found that oxygen-glucose deprivation/re-oxygenation (OGD/R) increased METTL3-dependent m 6 A modification of long non-coding RNA D63785 (lnc-D63785), thus causing reduced expression of lnc-D63785 ( Xu S. et al, 2020 ).…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%
“…Overexpression of m 6 A erasers can alleviate neuronal damage induced by I/R injury ( Xu S. et al, 2020 ). A third study found that oxygen-glucose deprivation/re-oxygenation (OGD/R) increased METTL3-dependent m 6 A modification of long non-coding RNA D63785 (lnc-D63785), thus causing reduced expression of lnc-D63785 ( Xu S. et al, 2020 ). Downregulation of lnc-D63785 further induces accumulation of miR-422a, which results in neuronal cell apoptosis ( Xu S. et al, 2020 ).…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%